Ancient Persia and Iranian Civilization - Huart, Clement, author.
1 online resource (272 pages)
Keywords: Originally published between 1920-70,The History of Civilization was a landmark in early twentieth century publishing. It was published at a formative time within the social sciences, and during a period of decisive historical discovery. The aim of the general editor, C.K. Ogden, was to summarize the most up to date findings and theories of historians, anthropologists, archaeologists and sociologists. This reprinted material is available as a set, in the following groupings, or as individual volumes: * Prehistory and Historical Ethnography Set of 12: 0-415-15611-4: £800.00 * Greek Civilization Set of 7: 0-415-15612-2: £450.00 * Roman Civilization Set of 6: 0-415-15613-0: £400.00 * Eastern Civilizations Set of 10: 0-415-15614-9: £650.00 * Judaeo-Christian Civilization Set of 4: 0-415-15615-7: £250.00 * European Civilization Set of 11: 0-415-15616-5: £700.00.